Association between long-term consumption trajectories of various foods and the risk of anxiety and depression in Chinese children - Qin Zhang; Yan Li; Jie Zhang; Di Wu; Zixuan Chen; Xinyi Feng; Qin Liu (Critical Public Health)
Mounting evidence suggests diets impact mental health, particularly anxiety and depression. This study aimed at determining the association between the choice of food and the risk of anxiety and depression among Chinese children. In survey research, a total of 987 children aged 13.5 ± 1.1 years were assessed for long-term consumption of six foods—smoked, fried, nutritious supplements, hormone-containing, high food additive, and out-of-season fruits and vegetables. The data were collected semi-annually over four years from 2015 to 2018. Anxiety and depression symptoms were evaluated in June 2019 using standardized screening tools. Latent Class Growth Modeling was used to categorize consumption trajectories, while logistic regression models was employed to analyze their associations. The prevalence of anxiety and depression was 14.0% and 14.9%, respectively. Chronic intake of foods with high levels of additives and excessive intake of nutritional supplements is associated with increased risks of anxiety (OR = 2.58, 95%CI [1.49, 4.47] and OR = 2.03, 95%CI [1.18, 3.49]) and depression (OR = 2.47, 95%CI [1.44, 4.23] and OR = 2.47, 95%CI [1.49, 4.10]) in children. Early and recent dietary patterns, particularly of fried foods and hormone-containing foods, are linked to anxiety symptoms (OR = 1.91, 95%CI [1.12, 3.25] and OR = 1.63, 95%CI [1.02, 2.59]) in children. Chronic intake of smoked foods and out-of-season produce may contribute to childhood depression (OR = 2.01, 95%CI [1.33, 3.03] and OR = 2.90, 95%CI [1.75, 4.80]). This study suggests that some specific foods may be associated with anxiety and depression in childhood, and it is necessary to pay attention to children’s diet health and timely intervene bad eating habits.